Splenic tuberculosis presenting as pyrexia of unknown origin - Hamizah, R; Rohana, AG; Anwar, SA; Ong, TZ; Hamzaini, AH; Zulkarnaen, AN (Medical Journal Malaysia, 2007)
We report a case of a previously healthy 38-year old lady who presented with prolonged fever and hepatosplenomegaly. Intensive investigations were performed for pyrexia of unknown origin which revealed negative. CT scan of the abdomen showed multiple hypodense lesions which did not respond to broad-spectrum antibiotics. Percutaneous biopsy of the splenic lesion revealed granuloma formation and Langhan's giant cells suggestive of TB. She responded well with anti- TB medication but required extended treatment duration of 24 months due to persistence of the splenic lesion on repeated CT scans. This case illustrates a very rare clinical entity of isolated splenic TB with a therapeutic dilemma following incomplete resolution, despite prolonged treatment.